Optimizing Continuous Integration and Delivery Pipelines in Mixed Java Version Environments: Challenges and Enterprise-Grade Solutions - Lars Holmberg (Academic Reseach Library for International Journal of Computer Science & Information System, 2026)
The evolution of software engineering practices has increasingly emphasized the need for robust, flexible, and scalable continuous integration and continuous delivery (CI/CD) pipelines. In enterprise contexts where legacy systems coexist with modern applications, managing heterogeneous Java environments poses significant challenges for automation, deployment, and quality assurance. This paper explores the theoretical foundations, architectural considerations, and practical implementations of CI/CD pipelines in non-containerized mixed Java version environments, focusing on enterprise-grade strategies and tools, with a particular emphasis on Jenkins-based implementations (Kathi, 2025). The study synthesizes insights from model-driven architecture, microservices integration, and DevOps methodologies to provide a comprehensive framework for pipeline optimization. Through critical analysis, the research evaluates existing paradigms, identifies technical bottlenecks in multi-version Java environments, and investigates solutions that balance automation efficiency, system reliability, and developer productivity. Methodologically, the study integrates literature synthesis with case-based evaluation, drawing on industry examples and empirical reports. Results highlight the significance of structured pipeline orchestration, modular testing frameworks, and adaptive deployment strategies that reconcile backward compatibility with performance optimization. The discussion expands on the implications for software architecture, emphasizing the necessity of cross-disciplinary integration between system design, security validation, and automated testing paradigms. Limitations regarding scalability in highly heterogeneous enterprise systems are acknowledged, and future research directions underscore the potential for AI-driven pipeline optimization, enhanced cross-platform modeling, and continuous quality assurance mechanisms. This research contributes to a nuanced understanding of CI/CD implementation in complex enterprise environments, offering both theoretical and practical guidance for software engineers, system architects, and organizational stakeholders seeking to optimize development workflows in multi-version Java contexts.